The Residual Effect of Prior Drop Jumps on Cardio Respiratory Parameters during Moderate Cycling in Young Women - Neringa Baranauskienė; Arvydas Stasiulis (Lithuanian Sports University, 2018)
Research background and hypothesis. Unaccustomed prior drop jumps (PDJ) can cause muscle damage with  concomitant delayed onset muscle soreness (DOMS) and decreased concentric contraction performance efficiency,  but  the  residual  effect  of  PJD  on  cardio  respiratory  system  parameters  during  moderate  cycling  exercise  (MC) remains equivocal. We suppose that DOMS, induced of PDJ, has altered cardio respiratory system parameters during  MC exercises. Research aim of the study was to assess the residual effect of 100 prior drop jumps on cardio respiratory system  parameters kinetics during moderate cycling exercise. Research methods. On four different days 10 women performed one increasing and three (control, 45 min and  24 h after 100 drop jumps) MC (Ergoline-800, Germany) exercises. The cadence of cycling was 70 rpm. The oxygen  uptake (2 oV& ), carbon dioxide output (2 co V & ); minute ventilation ( E V ) and heart rate (HR) were continuously recorded  during MC. Subjects rated their perceived exertions at the end of MC, and the DOMS was rated 24 h after PDJ. Research results. After 24 h the subjects felt moderate DOMS (5.0(2.79)) according to 10 point scale. The 2 oV& ; 2 co V & and HR kinetics were unaltered by moderate DOMS after 45 minutes and 24 hours, but  E V tended to increase 45  minutes after PDJ. The negative correlation between DOMS and  2 oV&  (r = -0.52) was observed. Discussion and conclusion. Prior drop jumps seem not to have significant residual effect on cardio respiratory  parameters kinetics after 45 minutes or 24 hours, but they tend to increase  E V  after 45 minutes of recovery during  moderate cycling exercise in young women. Keywords: delayed onset muscle soreness, oxygen uptake, constant load.